PELAKSANAAN UNDANG-UNDANG NOMOR 17 TAHUN 2014 TENTANG MASA RESES ANGGOTA DPRD PERSPEKTIF FIKIH SIYASAH : (Studi di DPRD Kota Makassar) - pu.tuuu, Putri Ayu Rasjid; A Rahman, Budiarti (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
This research aims to find out how I implement Law Number 17 of 2014 concerning the Recess Period for DPRD Members from a Siyasah Fiqh Perspective (Study in the Makassar City DPRD). The main problem is divided into several sub-problems, namely: How effective is the recess period for DPRD members in Makassar City and what are the obstacles and barriers to implementing the recess period in Makassar City. The research method used is through observation, interviews and documentation. The results of this research show that the effectiveness of the recess period for Makassar City DPRD members has been effectively carried out in formulating policies in Makassar City so that it is followed up in the form of government policy which results in the aspirations or complaints of the community being expressed in the finalized results of the DPRD recess. The obstacles and obstacles to implementing the recess period in Makassar City are, sometimes the policies issued are community-oriented which are produced by accommodating the aspirations that develop in the community, these activities are to accommodate the aspirations of the community which are carried out during the recess period. This activity is an obligation that DPRD members must carry out as a form of moral and political responsibility towards their constituents in accordance with the mandate of Law no. 23 of 2014 article 16, concerning the obligations of Regency/City DPRD members.